2003
DOI: 10.1177/146801730333004
|View full text |Cite
|
Sign up to set email alerts
|

Putting the Care into Residential Care

Abstract: There has been long-standing academic interest in the study of residential child care. Such study has made a valuable contribution to the development of both services and care practice. The perspectives of young people have, however, received less attention. This gap is most significant in relation to their group care experiences. Indeed the resident group is seen as a somewhat negative force and one from which children and young people require protection. This article uses data from one ethnographic study und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 6 publications
0
37
0
2
Order By: Relevance
“…Therefore, beyond the emotional discontinuities that characterize a family context of potential neglect, the transition to residential care is often associated with a sense of loss in the feeling of belonging and a sense of emptiness in the face to the unknown (Anaut, 2005;Spence & Matos, 2000). Thus, the way adolescents are welcome in the institution seems to make a difference in overcoming emotional barriers, and the role of significant figures such as the staff of the institution, peers and siblings is of special relevance (Beckett et al, 2006;Emond, 2003;Mota & Matos, 2010). Wekerle, Waechter, Leung, and Leonard (2007) suggested that the institutionalization affects the support network of adolescents, so most of the time, in face with the almost non-existent or discontinuous parental support, their support network is confined to figures from residential care.…”
Section: Attachment and The Role Of Siblings In Adolescents Under Resmentioning
confidence: 99%
“…Therefore, beyond the emotional discontinuities that characterize a family context of potential neglect, the transition to residential care is often associated with a sense of loss in the feeling of belonging and a sense of emptiness in the face to the unknown (Anaut, 2005;Spence & Matos, 2000). Thus, the way adolescents are welcome in the institution seems to make a difference in overcoming emotional barriers, and the role of significant figures such as the staff of the institution, peers and siblings is of special relevance (Beckett et al, 2006;Emond, 2003;Mota & Matos, 2010). Wekerle, Waechter, Leung, and Leonard (2007) suggested that the institutionalization affects the support network of adolescents, so most of the time, in face with the almost non-existent or discontinuous parental support, their support network is confined to figures from residential care.…”
Section: Attachment and The Role Of Siblings In Adolescents Under Resmentioning
confidence: 99%
“…For some, this theoretical position was intertwined with understandings of childhood as a socially constructed phenomenon and a commitment to enabling children to express their constructions of their world. In at least six of the studies, this led to a research design that included children's participation throughout, or at specific points of, the research process (Emond, 2003;Freundlich and others, 2006;Mason, 2008;Mullan and others, 2007;Renold and others, 2008;Warming, 2006). All of the participative projects were qualitative.…”
Section: The Integration Of Theory Into Research Designs and Reportingmentioning
confidence: 99%
“…Large residential establishments and clinics, where admission procedures, periods of intervention and types of intervention may be predictable, lend themselves to quasi-experimental studies and RCTs (see McNeal and others, 2006;Zegers and others, 2006). There are a small number of ethnographic studies of residential care that enable us to better understand peer-group dynamics and everyday living experiences (Abrams, 2006;Emond, 2003;Green, 2005;Torronen, 2006). Barter (2006), too, used observation alongside interviews and vignettes in residential homes.…”
Section: Range and Setting Of Research Designsmentioning
confidence: 99%
“…After all, peers are "often the only 'chosen' and free relationships" adolescents have in residential care (Emond, 2014, p. 200). In a residential setting, the peer group can also act as an important resource for learning and stimulation (Emond, 2003;Morgan, 2009;Nobre-Lima, 2009). …”
Section: Introductionmentioning
confidence: 99%